Biomedical waste management: assessment in health facility of a tertiary care teaching hospital in Jammu, union territory of Jammu and Kashmir, India - Sharma, Rakesh K.; Gupta, Rajiv K.; Kour, Harleen; Mahajan, Richa; Manhas, Sakshi; ., Sumaira; Zaffer, Imran; Hassan, Zahid Ul (International Journal Of Community Medicine And Public Health, 2022)
Background: Biomedical waste (BMW) management has, of late, emerged as an important health as well as environmental concern. It is imperative upon all the health facilities, irrespective of their size and number of patients catered, to ensure appropriate BMW management at all levels starting from its generation to its final disposal. The study intended to assess the management of BMW generated in one health facility of a tertiary care teaching hospital. Methods: The present cross-sectional study was conducted w.e.f. 1st January 2020 to 30th June 2020. The BMW generated in the Shri Maharaja Gulab Singh (SMGS) hospital-a health facility of government medical college (GMC) Jammu was collected at a designated place after its segregation. Then it was weighed before its transportation and final disposal. The BMW was weighed to generate monthly rates which were then converted to daily rates. Finally, BMW generation per bed per day was calculated. Results: It was found that BMW generated per bed per day was 0.197 kg. Infectious waste comprised 15% of the total whereas non-infectious component was 85%. The color-coded bags collection rate per day was 48.8 kg, 28.4 kg, 17.02 kg and 7.75 kg for yellow, red, blue and white containers, respectively. Conclusions: The authors found that the health facility was adhering to guidelines of BMW management. The need for continuous education and awareness promotion about BMW management among sanitation workers, nurses, technicians and doctors cannot be underestimated.